Early Neolithic pottery dispersals and demic diffusion in southeastern Europe - Mihael Budja (Documenta Praehistorica, 2009)
The 14C gradient of pottery dispersal suggests that the sites in the southern Balkans are not significantly older than those in the northern and eastern Balkans. A gradual demic diffusion model from south to north and a millennium time span vector thus find no confirmation in the set of AMS 14C dates and associated contexts that mark pottery dispersal within Southeastern Europe. The first ‘demic event’ that was hypothesised to reshape significantly European population structure and generate a uniform process of neolithisation of southestern Europe has no confirmation in frequency of Y-chromosome subhaplogroups J2b and E3b1 distribution within modern population in Southeastern Europe.